Sertifikasi Produk Halal: Studi Perbandingan Indonesia dan Thailand - Aminuddin, Muh. Zumar (SHAHIH : Journal of Islamicate Multidisciplinary, 2016)
AbstractThis research is intended to describe the relationship between religion and State in handling the Halal products certification in Indonesia and Thailand. Halal certification in Indonesia was initially civil society movement that supported by the state, which is taken by LPPOM MUI. The main objective was to protect Muslim from Haram products. However, by coming out of law no. 33 2014 about halal product guarantee, the halal certification will be carried out by the state institution, that is Security Agency Halal Products known as BPJPH. While in Thailand, Halal product certification is the authority of Central Islamic Council of Thailand (CICOT) which is similar to the Indonesian Ulema Council (MUI). In Thailand, Halal product certification has much giving supports to the government economic, especially for the purpose of exporting food to the Muslim countries and also to attract Muslim tourist to visit Thailand. Keywords: Religion, Country, Halal Certification AbstrakPenelitian ini dimaksudkan untuk mendeskripsikan hubungan antara agama dan negara dalam penanganan sertifikasi produk halal di Indonesia dan Thailand. Indonesia pada awalnya sertifikasi halal merupakan gerakan civil society yang didukung negara, yaitu LPPOM MUI. Tujuan utamanya adalah melindungi umat islam dari barang-barang haram. Namun dengan keluarnya Undang-undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal, penanganan sertifikasi halal akan dilakukan oleh lembaga negara, yaitu Badan penyelenggara Jaminan Produk Halal (BPJPH). Sedangkan di Thailand sertifiksi halal menjadi wewenang penuh Central Islamic Council Of Thailand (CICOT), semacam MUI di Indonesia. Di Thailand sertifikasi produk halal sangat membantu negara di sektor ekonomi, terutama untuk kepentingan ekspor makanan ke negara-negara muslim serta menarik wisatawan muslim ke Thailand. Kata Kunci: Agama, negara, sertifikasi halal